Inventory Management Policies for Maintenance Spare Parts: Integration of Analytic Hierarchy Process and Multicriteria ABC Classification in the Plastics Industry - Londoño Ortega, Julio César; Martínez Escobar, Nathaly; Rodríguez González, Paola Andrea (International Journal of Integrated Engineering, 2025)
This study establishes supply management policies for maintenance spare parts in a plastics transformation company, using a methodology applicable to any industry managing spare parts inventories. It addresses the challenges of excessive inventory levels and the lack of objective rules for defining stock quantities and parameters by applying a multicriteria approach based on AHP and ABC classification, incorporating expert judgment through the Delphi method. The classification assigned the highest weight to criticality (0.683), followed by supply (0.2) and maintenance (0.117), ensuring a balanced evaluation. Demand analysis revealed that 69% of spare parts exhibit erratic demand, 39% have no recorded demand, and only 145 out of 3,842 items show stable demand, allowing the application of double exponential smoothing forecasting techniques. Based on these findings, a periodic inventory review system was implemented with demand-adjusted policies: (R, S) with safety stock (IS) for class A and B items with stable demand and adjusted IS levels or stock elimination for erratic demand items when justified. This strategy led to a 30% reduction in excess stock and a 15% increase in spare parts availability, optimizing costs and operational efficiency. Additionally, the study highlights the importance of establishing shared indicators between logistics and maintenance, maintaining accurate demand records, and centralizing spare parts storage to enhance decision-making and minimize downtime. These findings contribute to improving inventory management and reducing operational disruptions in industrial environments.